Audit Energi pada Gedung Lecture Building Universitas Udayana - Nugraha, I Komang Krisna Bayu; Sukerayasa, I Wayan; Setiawan, I Nyoman; Janardana, I Gusti Ngurah; Budiastra, I Nyoman; Suartika, I Made (Innovative: Journal Of Social Science Research, 2025)
Increasing electrical energy consumption in the education sector requires efforts to save on campus buildings. This study aims to identify efficiency opportunities in the Lecture Building of Udayana University using the walk-through audit method. Measurements were made on lighting, air conditioning (AC), elevators, and pumps using lux meters, infrared thermometers, and power quality analyzers. The results showed that the biggest savings came from the air conditioning system of 22,965 kWh/month (15.47% efficiency) through temperature and operating time adjustments. The energy consumption intensity (IKE) value was recorded at 54,145 kWh/m²/year for one floor and 18,048 kWh/m²/year for three floors, far below the standard of 240kWh/m²/year. The other system generates technical recommendations to support the sustainable implementation of green campuses.